The perceived impact of the Covid-19 epidemic: evidence from a sample of 4807 SMEs in Sichuan Province, China - Lu, Yi; Wu, Jing; Peng, Junlin; Lu, Li (Environmental hazards, 2020)
The outbreak of the coronavirus disease (Covid-19) in January 2020 in Wuhan has had a significant impact on the Chinese economy, and especially on the small and medium-sized enterprises (SMEs). In February 2020 an online questionnaire and follow-up interviews were conducted on 4807 SMEs in Sichuan to assess the challenges associated with work resumption and the associated policy requirements. It was found that most SMEs were unable to resume work because of a shortage of epidemic mitigation materials, the inability of employees to return to work, disrupted supply chains, and reduced market demand. Many SMEs were also facing cash flow risks as they had to continue to pay for various fixed expenditures even though they had little or no revenue. As these delays in work resumption have put unprecedented pressures on the survival of many SMEs, recommendations relevant to China and other affected countries regarding cash flow relief, work resumption and consumption stimulation are given to assist SME survival and economic recovery from the disaster situation.